Factors That Influence Nurses' Work-Family Conflict, Job Satisfaction, and Intention to Leave in a Private Hospital in Turkey - Dilek Ekici; Kamuran Cerit; Tugba Mert (Baqiyatallah University of Medical Sciences, 2017)
Introduction: Nurses who have difficulty balancing their family role and responsibilities because of intense work pressure tend to leave their current jobs to work in organizations which offer better working conditions, lower workloads, and more managerial support. Objective: This study aimed to determine nurses' work-family conflict (WFC), job satisfaction, and intention to leave the job in a private hospital. Methods: This descriptive study is based on a methodological and causal research design. The population of the study included 98 nurses working in a private hospital. The research model is tested with structural equation modelling (SEM). Results: Nurses working changing shifts reported statistically higher levels of work-to-family conflict and workload than those consistently working daytime shifts. Managerial support and workload explained 48% of WFC. Work structure alone explained 44% of job satisfaction. Job satisfaction and WFC explained 17% of the variance in intention to leave. Conclusion: Nurses who have difficulty balancing their family roles and responsibilities because of intense work pressure tend to leave their current jobs to work in organizations which offer better working conditions, lower workload, and more managerial support. The work structure of nurses should be reorganized in order to enhance nurses' job satisfaction.